Supporting urban parking management with GeoMedia Professional - António Fernando Vasconcelos Cunha Castro Coelho (2005)
Private transport management assumes more and more a key role in urban planning and management. This paper presents a new custom application, specifically developed for the decision maker, which provides a set of functionalities regarding public parking management, pricing policies and land use management. This instrument will provide the ability to test the impact of different parking solutions, different parking prices and different land uses for a study area. As a result, several indicators will be provided, such as parking occupancy and parking pressure for a certain area and time of analysis.